Special deductions and the hiring of people with disabilities, the effect of ignorance in private companies in Ecuador - Espinosa-Jaramillo, María Teresa; Ricón-Castillo, Elita Luisa (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
To date, the tax reform has gone through several modifications allowing the collection of taxes for the provision of public services, among the changes in the law there have always been tax benefits for hiring employees with disabilities, thus achieving a mutual benefit for both the state and the taxpayer. In particular, the Labour Code was analysed with regard to work for persons with disabilities hired only in the private sector. Equal and dignified employment by promoting the integration of people with disabilities into the labour market, together with existing tax incentives such as tax deductions for both employers and employees. The lack of awareness of these incentives is taken into account due to the low number of private companies that enjoy this benefit and also to the low number of people with disabilities hired. The purpose of this research is to inform in a more simplified way the benefits that companies do not enjoy due to lack of knowledge, making a brief comparison and analysis to promote the right to equal work. This article is developed under a descriptive research methodology with a study technique and comparative analysis based on data from Ecuador.